China's "soft power" re-emergence in Southeast Asia - Johannes Dragsbaek Schmidt (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2006)
China's "soft power" re-emergence in Southeast Asia Johannes Dragsbaek Schmidt Associate Professor Research Center on Development and International Relations Aalborg University Email. jds@ihis.aau.dk ABSTRACT Globalization is rapidly changing the overall structure of the international division of labor with the shift of services and manufacturing from the old industrialized economies to the new emerging giants - the global office platform in India and the global factory floor in China. This dislocation in production, services and manufacturing signifies a challenge which might be more important, but nevertheless part and parcel of the inherent imbalances in the world economy. Until recently there has been much academic and layman attention on over-production, growing inequalities, the increasing North-South gap, the roaring conflicts over energy and raw materials including oil and water, turbulence and crisis in the international financial system, and not least the fact that the present phase of capitalism has led to jobless growth in the established core economies in Europe and the United States. The question for the international political economy is where and how do countries like India and China fit in? Keywords: Globalisation, Regionalism, Bilateralism, Diaspora, USA, China, Southeast Asia
hdl:10398/7407
Keywords: 330; globalisering; international politik; diaspora; regionalisering; sydøstasien; kina; usa